Terpenoids from the Stem bark of Aglaia elaeagnoidea and their cytotoxic activity against HeLa and DU145 Cancer Cell lines - Dini Oktaviani; Winda Sukmawati; Kindi Farabi; Desi Harneti; Nurlelasari Nurlelasari; Darwati Darwati; Rani Maharani; Tri Mayanti; Agus Safari; Unang Supratman (Universitas Jenderal Soedirman, 2022)
Aglaia is the largest genus of the Meliaceae family which contains terpenoid compounds. This type of compounds showed a diverse structures and biological activities that can be found in natural resources. Aglaia elaeagnoidea is a species from Aglaia genus that only has a few previous research. This study was aimed to isolate and determine the chemical structure of terpenoid compounds from the ethyl acetate extract of A. elaeagnoidea stem bark. Ethyl acetate extracts were separated and purified by various chromatographic techniques to obtain compounds 1-5. Compounds 1-5 were identified their chemical structures by spectroscopic methods (IR, MS, and NMR) and comparison with previous reported spectral data. Compounds 1 and 2 were identified as eudesmane-type sesquiterpenoids, 5-epi-eudesm-4(15)-ene-1β,6β-diol (1) and 6α-Hydroxy-eudesm-4(15)-en-1-one (2). Compounds 3-5 were identified as dammarane-type triterpenoids, 20S,24S-epoxy-25-hydroxydammarane-3-one (3), 20S,24S-epoxydammarane-3α,25-diol (4), and 3α-epi-cabraleahydroxy lactone (5). These compounds are first time reported from this plant. Compounds 1-5 were tested for cytotoxicity against HeLa cervical cancer cell and DU145 prostate cancer cell and as a result, compound 4 (20S,24S-epoxydammarane-3α,25-diol) showed the stronger activity compared to other compounds.